Effectiveness of structured, multidisciplinary long-term care for pediatric cancer survivors: protocol of the multicenter, randomized-controlled AELKI study - Schmidt, Hannah; Baust, Katja; Calaminus, Gabriele; Hohls, Lisa; Tetzner, Katharina; Griech, Nicole; Haugke, Henrike; Baltus, Hannah; Elsner, Susanne; Katalinic, Alexander; Becker, Hera; Cytera, Chirine; et al. (Trials, 2024)
Background: In Germany, around 2.250 children and adolescents are diagnosed with cancer each year. Despite generally positive long-term survival rates, many patients must cope with late effects of the disease and its treatment. This highlights the need for a well-structured, long-term approach addressing both physical and mental health issues. Currently, the German healthcare system lacks such comprehensive structures. Our study aims to evaluate the effectiveness of a structured, multidisciplinary long-term approach compared to conventional “treatment as usual” (TAU). Methods: A prospective, multicenter study with ten pediatric university clinics in Germany will be conducted. The cluster-randomization takes place at the clinic level. Children and adolescents who completed their cancer treatment at least five years ago and their parents will be eligible to participate. While the control group (CG) receives TAU, the intervention group (IG) participates in a structured program. This program includes risk-based medical treatment and psychosocial interventions tailored to each patient’s individual needs within a two-month timeframe. The primary outcome is the improvement of self-efficacy. Secondary outcomes are satisfaction with health care, improvement of health-related quality of life (HRQoL), reduction of mental health problems, and improvement of transition readiness. Discussion: This approach has the potential to optimize the health care for individuals who survived cancer during childhood or adolescence. It addresses the challenges of overuse, underuse, and misuse of health care resources. By considering both medical and psychosocial factors and promoting increased self-efficacy, independent from parental involvement, it may facilitate a smoother transition to adult medicine and enhance adherence to lifelong aftercare. If proven successful, this approach will contribute to the integration of multidisciplinary strategies into standard healthcare practice. Trial registration: German Clinical Trials Register DRKS00029269. Registered on December 23, 2022.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Cancer; Children and adolescent; Long-term care; Multidisciplinary; Psychosocial